Analisis Gaya Kepemimpinan Kepala Desa dalam Penyelesaian Konflik Perkebunan di Desa Air Buluh Kecamatan Ipuh Kabupaten Mukomuko - Cahyani, Awalia Dwi; Rosidin, Rosidin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study discusses the leadership style of the village head in conflict resolution. Conflict over land use and ownership is an important point between the community and the company. The root of the conflict that occurred between the community and the company was due to the understanding between the two parties. Based on this, this study aims to find out how the Village Head's Leadership Style in Resolving Conflicts with Plantations in Air Buluh Village, Ipuh District, Mukomuko Regency. This study uses a qualitative approach with descriptive qualitative types. The research location is at the Air Buluh Village Office, Ipuh District, Mukomuko Regency. The research subjects were village heads and informants were village officials, community leaders, companies and the sheltered community. Data collection techniques using observation techniques, interviews and documentation. From the analysis that the author did, it can be concluded that the leadership style of the head of Air Buluh village in resolving conflicts between the community and plantations in Air Buluh Village, Ipuh District, Mukomuko Regency applies a Democratic leadership style. joint decision.